Rapid‐run ionosonde observations of traveling ionospheric disturbances in the auroral ionosphere. Issue 8 (13th August 2013) - Kozlovsky, Alexander; Turunen, Tauno; Ulich, Thomas
Abstract: [1] Since 2007, the Sodankylä Geophysical Observatory routinely performs vertical ionosphere soundings once per minute, using a frequency‐modulated continuous‐wave chirp at the rate of 500 kHz/s from 500 kHz to 16 MHz. We used these data to study traveling ionospheric disturbances (TIDs) during 10–16 local time. The observations were made between April 2007 and June 2012, mostly during low solar activity. The TIDs were studied in five bands of periods corresponding to the following: infrasonic (acoustic) waves and the buoyancy cutoff (periods from 5 to 10 min); small‐scale gravity waves (GWs; 10–15 min); medium‐scale (MS; 15–30 min) GWs; medium‐large scale (MS‐LS; 30–60 min) GWs; and large‐scale (LS; 60–120 min) GWs. Relative contribution (with respect to LS TIDs) of the short‐period (5–15 min) and MS (15–30 min) TIDs shows minima in winter and maxima in summer. These annual variations anticorrelate with variations of true height, namely, the largest relative amplitudes occur in summer, when TIDs were observed at minimal heights. We suggest that the summer increase of shorter‐period TIDs is due to lowering reflection to the height where the Brunt‐Väisälä period is smaller and, hence, shorter‐period gravity waves exist. The summer maxima were most prominent during the 3 years of minimal solar activity (2008–2010). In 2011, when solar activity increased, the annual variation seems less prominent. Annual variations of the longer‐period (30–120 min) TIDs are essentially less significant. For all TIDs, no obvious dependences on the AE and Ap indices of magnetic activity were found. Key Points: Continues rapid‐run (1‐minute) ionosonde observations at auroral latitude Statistics of travelling ionospheric disturbances of 5 min to 2 hours periods TID dependency on season, auroral electrojet, and magnetic activity